Best practices for educating NICU nurses about palliative care: A rapid review. Issue 1 (February 2022) - St Louis, Julia Renee; Pesut, Barbara; Zhao, Rachel
Abstract: Introduction: Nurses in neonatal intensive care units (NICUs) provide more direct care at the end-of-life than other health care providers, yet report feeling inadequately prepared for neonatal palliative care. The purpose of this review was to identify studies testing educational interventions for palliative care to NICU nurses. Methods: Rapid Review Results: Four studies reported education interventions lasting 6–21 h with 30–142 participants. All used convenience samples and pre/posttest designs. A variety of outcome measures were used, including objective knowledge tests and structured clinical observations. The studies showed statistically significant improvements in at least one outcome, although these results should be viewed cautiously because of less rigorous study designs. Discussion: The small number of studies identified indicates a need to implement and evaluate further educational interventions. While the evidence from these studies suggested positive outcomes, additional studies using more rigorous research methods are needed.